PENGEMBANGAN APLIKASI KUESIONER BERBASIS WEB - Danispadmanaba Y., Nicholaus
One of the most promising technologies in the field of questionnaire digitalization is web-based application technology. This technology offers a variety of automation opportunities in each phase of questionnaire-based survey process, which consists of survey design, survey instrument development, survey execution, and data analysis and survey results reporting phase. Automation in each survey phase would assist all parties that participate in a survey process, which consist of survey organizers and respondents, and reduce the chance of human error when compared to other types of technology, such as desktop application (e.g., Microsoft Excel). Besides, a variety of existing web-based questionnaire applications can be found, such as: Typeform, Qualtrics, SurveyMonkey, and Google Forms. Unfortunately, digitalization on survey design and data analysis and survey results reporting phase is often overlooked by existing web-based questionnaire applications. Therefore, the purpose of this research is to develop a web-based questionnaire application that is able to facilitate both survey organizers and respondents in each phase of online survey process from survey design until data analysis and survey results reporting phase. Literature review and observation of benchmark applications are done to create user and system requirements. Those requirements then become the basis for process and structural design of the system. The implementation of those designs is a web-based application that consists of server and client components that are built with high concurrency in mind. Testing shows that the developed application is able to fulfill both functional and non-functional requirements. Besides, testing also shows that the developed questionnaire application is easier to use when compared to 3 out of 4 benchmark applications based on time spent and errors committed by users.